Developing Socioemotional Skills for the Philippines' Labor Market - Acosta, Pablo; Igarashi, Takiko; Olfindo, Rosechin; Rutkowski, Jan (Washington, DC: World Bank, 2017)
While the Philippines has achieved remarkable progress in raising the education level of its labor force, the standard proxy for educational attainment—years of formal schooling—is increasingly inadequate as a measure of workforce skills. About one-third of employers report being unable to fill vacancies due to lack of applicants with the requisite skills. Most of these “missing skills” are socioemotional skills,” also known as “non-cognitive skills”, “soft skills” or “behavioral skills.”